2014
DOI: 10.1142/s0217984914501735
|View full text |Cite
|
Sign up to set email alerts
|

High extraction efficiency inGaN-based light-emitting diodes with air-hole photonic crystal slab

Abstract: In this paper, extraction efficiency in simplified and layered light-emitting diodes (LEDs) of GaN photonic crystal with periodic air holes is studied by three-dimensional finite-difference time-domain method. Photonic band structures of the photonic crystal are obtained by plane-wave expansion method. The results about simplified GaN -LED show that extraction efficiency is very sensitive to the structure parameters tuning, and increases considerably inside the transverse-electric-like gap region. A maximum ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has been reported that periodic patterns on GaN-based LED are more effective to enhance the light output power than non-periodic patterns such as a surface roughness due to light waveguide through the effective medium 2324. To fabricate PHP on nanometer scale, nanoimprint lithography, direct holographic photodissolution, and laser interference lithography are commonly applied 252627282930. According to previous reports on LEDs with PHPs, research groups mainly investigated the photonic crystal effect on LEE improvement 31323334…”
mentioning
confidence: 99%
“…It has been reported that periodic patterns on GaN-based LED are more effective to enhance the light output power than non-periodic patterns such as a surface roughness due to light waveguide through the effective medium 2324. To fabricate PHP on nanometer scale, nanoimprint lithography, direct holographic photodissolution, and laser interference lithography are commonly applied 252627282930. According to previous reports on LEDs with PHPs, research groups mainly investigated the photonic crystal effect on LEE improvement 31323334…”
mentioning
confidence: 99%
“…Therefore, the external radiation efficiency of ordinary LEDs is only about 3%. [5][6][7][8] In addition to the low monochromaticity of LED lights, high costs, potential damage to human eyes, and other drawbacks, this presented a significant barrier to the development of future lighting technologies. Consequently, boosting the light extraction efficiency (LEE) of LEDs is vital for replacing current lighting sources, and research linked with this endeavor is critical for speeding the expansion of the present lighting sector.…”
Section: Introductionmentioning
confidence: 99%
“…After repeated reflections from the medium around it, the majority of the light released from the general LED luminous center is not properly radiated from the LEDs, which results in the light radiation efficiency being very poor. Therefore, the external radiation efficiency of ordinary LEDs is only about 3% 5–8 . In addition to the low monochromaticity of LED lights, high costs, potential damage to human eyes, and other drawbacks, this presented a significant barrier to the development of future lighting technologies.…”
Section: Introductionmentioning
confidence: 99%